Recent advances in upper gastrointestinal lymphomas: molecular updates and diagnostic implications. Issue 1 (31st December 2020) - Foukas, Periklis G; Bisig, Bettina; de Leval, Laurence
Abstract : Approximately one‐third of extranodal non‐Hodgkin lymphomas involve the gastrointestinal (GI) tract, with the vast majority being diagnosed in the stomach, duodenum, or proximal small intestine. A few entities, especially diffuse large B‐cell lymphoma and extranodal marginal zone lymphoma of mucosa‐associated lymphoid tissue, represent the majority of cases. In addition, there are diseases specific to or characteristic of the GI tract, and any type of systemic lymphoma can present in or disseminate to these organs. The recent advances in the genetic and molecular characterisation of lymphoid neoplasms have translated into notable changes in the classification of primary GI T‐cell neoplasms and the recommended diagnostic approach to aggressive B‐cell tumours. In many instances, diagnoses rely on morphology and immunophenotype, but there is an increasing need to incorporate molecular genetic markers. Moreover, it is also important to take into consideration the endoscopic and clinical presentations. This review gives an update on the most recent developments in the pathology and molecular pathology of upper GI lymphoproliferative diseases.